Bacterial diversity and functional interactions between bacterial strains from a phenanthrene-degrading consortium obtained from a chronically contaminated-soil - Festa, Sabrina (2013)
A phenanthrene-degrading consortium (CON-Phe) was obtained from a chronically contaminated soil. The consortium degraded 58% of the phenanthrene supplied during the first 7 days of incubation with the concomitant accumulation of 1-hydroxy-2-naphthoic acid (HNA). The composition of CON-Phe and its dynamic during phenanthrene degradation were determined using culture-dependent and independent approaches (polymerase chain reaction-denaturing gradient gel electrophoresis and clone libraries). Among the detected bacteria by both methods, Sphingomonadaceae family frequently occurred, but some genera were only observed through culture-dependent methods (Enterobacter sp. and Pseudomonas sp.) and others only through culture-independent methods (Ochrobacterium sp., Alcaligenes sp.). Five different strains were isolated and identified; between them only the strain AM (Sphingobium sp.) showed phenanthrene degradation. And only in strains AM and B (Enterobacter sp) evidence of the presence of PAH-ring hydroxylating dioxygenases genes was found. In order to determine the role of the isolated strains in the CON-Phe and the interaction between them, the phenanthrene degradation by defined mixed cultures was studied. All the defined consortia, formed by strain AM together with another of the isolated strains, showed percentages of phenanthrene biodegradation significantly higher than the strain AM alone and the natural consortia. In addition, no accumulation of HNA was observed in these defined consortia. These results might suggest that in the soil consortia the competition between the species and the community dynamics could cause a negative effect in the phenanthrene degradation. On the other hand, a synergistic effect between the phenanthrene-degrading strain AM and the other isolated strains was observed.